Analysis of Pregnant Women, their Newborn Infants, and Maternal-Fetal Transmission of COVID-19 admitted in Tertiary Hospital, Patiala, Punjab - Ramandeep Kaur Bajwa (International Journal of Nursing Research, 2024)
Aims and Objectives: The aim of the study was to find the clinical characteristics of pregnant women, their newborn infants, and maternal-fetal transmission of coronavirus disease 2019 (COVID-19). Materials and Methods: Study design was cross-sectional design. The setting included all the mothers admitted in labor room and their infants in the month of July-August 2020 in Government Rajindra Hospital, Patiala. The study sample included total 574 (July in 282 and 292 in August) pregnant mothers (60 COVID-19 positive mothers) and their infants admitted during the month of July-August 2020. Mothers and neonatal data were collected from mother’s record and child files from neonatal intensive care unit. Results: A total of 60 infected antenatal mothers with COVID were reported. Confirmation by reverse transcription polymerase chain reaction test shows that throat swab for two newborns were positive for COVID-19. Conclusion: The risk of vertical transmission is small. Majority of the newborns remain asymptomatic with good clinical outcome. The findings from this study can guide and enhance prenatal counseling of women with COVID-19 infection occurring during pregnancy.